2019
DOI: 10.1016/j.molcel.2018.10.022
|View full text |Cite
|
Sign up to set email alerts
|

ATP-Dependent Dynamic Protein Aggregation Regulates Bacterial Dormancy Depth Critical for Antibiotic Tolerance

Abstract: Graphical Abstract Highlights d The degree of drug-tolerant cells being dormant can be measured by ''dormancy depth'' d Cellular dark foci, proved to be protein aggresomes, indicate dormancy depth d Depletion of intracellular ATP is the major force driving aggresomes formation d DnaK is vital in the disaggregation of aggresomes when a dormant cell resuscitates In this work, Pu et al. introduced a concept of ''dormancy depth'' that provides a unifying framework for understanding both persisters and viable but n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
329
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(366 citation statements)
references
References 46 publications
32
329
2
3
Order By: Relevance
“…By inhibiting the activity of ribosomes, we have developed means to convert E. coli cells into a 20 population that consists solely of persister cells (6) so that insights may be made about persister cell resuscitation. Using this approach, which has been verified by six independent labs to produce bona fide persister cells (7)(8)(9)(10)(11)(12), we have shown that persister cells resuscitate rapidly primarily in response to external signals (13), such as fresh nutrients, rather than stochastically (14). Critically, persister cell resuscitation is heterogeneous and depends on the number of active ribosomes; once a threshold of active ribosomes is reached, persister cells elongate and divide (13).…”
Section: Introductionmentioning
confidence: 71%
“…By inhibiting the activity of ribosomes, we have developed means to convert E. coli cells into a 20 population that consists solely of persister cells (6) so that insights may be made about persister cell resuscitation. Using this approach, which has been verified by six independent labs to produce bona fide persister cells (7)(8)(9)(10)(11)(12), we have shown that persister cells resuscitate rapidly primarily in response to external signals (13), such as fresh nutrients, rather than stochastically (14). Critically, persister cell resuscitation is heterogeneous and depends on the number of active ribosomes; once a threshold of active ribosomes is reached, persister cells elongate and divide (13).…”
Section: Introductionmentioning
confidence: 71%
“…Furthermore, our method has been used to (i) determine that persister cells wake via ribosome activation (Kim et al, 2018b) and (ii) by activating chemotaxis (Yamasaki et al, 2019), (iii) show that the cells capable of resuscitation in a viable but not culturable population are equivalent to persister cells (Kim et al, 2018a), (iv) identify compounds that kill persister cells and (v) reveal that the alarmone ppGpp directly creates persister cells by stimulating ribosome dimerization . In addition, our method to generate a high population of persister cells has been utilized by at least six independent groups (Grassi et al, 2017;Cui et al, 2018;Narayanaswamy et al, 2018;Sulaiman et al, 2018;Tkhilaishvili et al, 2018;Pu et al, 2019).…”
Section: Bpoet Resuscitates E Coli Persister Cellsmentioning
confidence: 99%
“…The persister cells generated in this way have been (i) confirmed eight ways (19), (ii) used to determine that persister cells wake via ribosome activation (19) and chemotaxis (20), (iii) used to show that the cells capable of resuscitation in a viable but not culturable 95 population are equivalent to persister cells (15), (iv) used to identify compounds that kill persister cells (27), and (v) used to show that the alarmone ppGpp directly creates persister cells by stimulating ribosome dimerization (16). In addition, our method to generate a high population of persister cells has been utilized by at least six independent groups (28)(29)(30)(31)(32)(33).…”
Section: Resultsmentioning
confidence: 99%